Copper‐Catalyzed [2+2+1+1] Annulation for the Regioselective Synthesis of 2, 6‐Diarylpyridines via C1‐Insertion and Subsequent Cyclization. Issue 32 (27th August 2020) - Vodnala, Nagaraju; Gujjarappa, Raghuram; Satheesh, Vanaparthi; Gupta, Richa; Kaldhi, Dhananjaya; Kabi, Arup K.; Malakar, Chandi C.
Abstract: Copper‐catalyzed [2+2+1+1] annulation strategy has been investigated for the regioselective synthesis of symmetrical and unsymmetrical 2, 6‐diarylpyridines using aliphatic amines as nitrogen source and DMSO as C1‐synthon. The developed protocol was successful for the transformation of non‐activated aromatic ketones and non‐activated aliphatic amines into 2, 6‐diarylpyridines via an "easy to access" approach. This protocol has been verified on wide range of substrates having various functional groups. Abstract : A copper‐catalyzed [2+2+1+1] annulation protocol has been described via C1‐insertion and subsequent cyclization towards the comprehensive synthesis of 2, 6‐diarylpyridines in good yields and selectivity using aliphatic amines as nitrogen and DMSO as C1 sources.